2021
DOI: 10.1159/000517486
|View full text |Cite
|
Sign up to set email alerts
|

Oncologists’ Perceptions of Tumor Genomic Profiling and the Communication of Test Results and Risks

Abstract: Tumor genomic profiling (TGP) identifies genetic targets for precision cancer treatments. The complexity of TGP can expose gaps in oncologists’ skills, complicating test interpretation and patient communication. Research on oncologists’ use and perceptions of TGP could inform practice patterns and training needs. To study this, a sample of oncologists was surveyed to assess TGP use, perceptions, and perceived skills in TGP interpretation/communication, especially in communication of hereditary risks. Genomic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 20 publications
2
23
0
Order By: Relevance
“…6 Health care professionals would ultimately need to translate that information for their patients. Two studies, from the US 73 and Australia, 74 examined the perceptions of oncologists in interpreting genomic profiling information. Participants in both studies revealed that although they felt confident in their understanding of testing, using results to inform treatments, and explaining the technology to patients, they reported less confidence in interpreting more complex findings or information about secondary mutations.…”
Section: Interpreting Complex Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Health care professionals would ultimately need to translate that information for their patients. Two studies, from the US 73 and Australia, 74 examined the perceptions of oncologists in interpreting genomic profiling information. Participants in both studies revealed that although they felt confident in their understanding of testing, using results to inform treatments, and explaining the technology to patients, they reported less confidence in interpreting more complex findings or information about secondary mutations.…”
Section: Interpreting Complex Resultsmentioning
confidence: 99%
“…Participants in both studies revealed that although they felt confident in their understanding of testing, using results to inform treatments, and explaining the technology to patients, they reported less confidence in interpreting more complex findings or information about secondary mutations. 73,74 Oncologists also reported that they would benefit from receiving additional training about interpreting tests results and communicating more complex findings to patients. 73,74 Increased recruitment and additional training for health care professionals specializing in genetics (including oncologists and genetic counsellors) have been recommended in Canada as demand for genetic services continues to increase.…”
Section: Interpreting Complex Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Future research may also consider investigating whether information about TGP from more trusted health information sources, such as Black and AA healthcare providers, community organizations (e.g., faith-based organizations), and family members [ 68 ], could mitigate the association between medical mistrust and TGP concerns. Finally, one potential strategy for mitigating some of the disparities in cancer outcomes includes improved communication strategies for relaying cancer-related and genetic testing-related information to cancer patients with high medical mistrust and potentially limited health literacy [ 38 ]. For example, researchers have developed tailored methods of communicating more effectively with patients with lower levels of health literacy about TGP [ 69 ], including specialized training programs for health professionals [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, higher levels of cancer health literacy are inversely related to number of inpatient hospitalizations and length of hospitalization stays [ 37 ]. However, given the disproportionately lower rates of TGP use among Black and AA cancer patients and the lower levels of genetic literacy, understanding the specific barriers patients face during their cancer treatment should be addressed to close the health disparities gap [ 38 ].…”
Section: Introductionmentioning
confidence: 99%